Cost-effectiveness and affordability evaluation of a residential prototype built with compressed earth bricks, hybrid roofs and palm midribs - Abdel Gelil Mohamed, Nermine; Abo Eldardaa Mahmoud, Islam (Frontiers in Built Environment, 2023)
In an effort to contribute practically to Sustainable Development Goal 11 (Sustainable Cities and Communities), a residential prototype incorporating alternative technologies was built in Egypt in response to the widespread reliance on materials with high environmental impact in the construction sector. In order to reduce the usage of steel, fired bricks, cement, and imported wood, the house incorporates enhanced vernacular technologies recognized in a number of countries for their affordability and sustainability. The current paper focuses on the house's construction cost-effectiveness and price affordability, while calculating also the savings in the quantities of materials. Interlocking compressed stabilized earth brick walls, partially reinforced, jack arch and funicular shell roofs, and date palm midribs were employed. With the scarcity of available information in the literature, the research offers rigorous real-world data on material quantities, labor and costs, and compares them to conventional methods. According to the findings, walls cut costs by half, roofs by a quarter, and midribs by two-thirds; the alternatives combined saved 45%, and the house saved a quarter of the cost after adding common expenses. Moreover, less than one-third of steel, fired bricks, and cement were utilized. In the Egyptian context of government-built houses, the prototype would be affordable for most Egyptian income brackets while the conventional house was expensive for the lowest three. The findings provide empirical support for the economic advantages of enhanced vernacular technologies to address residential affordability and sustainability, and ultimately SDG11.